IBM Cloud Pak for Data - Manda, Hemanth; Srinivasan, Sriram; Rangarao, Deepak (Packt Publishing, 2021)
Build end-to-end AI solutions with IBM Cloud Pak for Data to operationalize AI on a secure platform based on cloud-native reliability, cost-effective multitenancy, and efficient resource management Key Features Explore data virtualization by accessing data in real time without moving it Unify the data and AI experience with the integrated end-to-end platform Explore the AI life cycle and learn to build, experiment, and operationalize trusted AI at scale Book Description Cloud Pak for Data is IBM's modern data and AI platform that includes strategic offerings from its data and AI portfolio delivered in a cloud-native fashion with the flexibility of deployment on any cloud. The platform offers a unique approach to addressing modern challenges with an integrated mix of proprietary, open-source, and third-party services. You'll begin by getting to grips with key concepts in modern data management and artificial intelligence (AI), reviewing real-life use cases, and developing an appreciation of the AI Ladder principle. Once you've gotten to grips with the basics, you will explore how Cloud Pak for Data helps in the elegant implementation of the AI Ladder practice to collect, organize, analyze, and infuse data and trustworthy AI across your business. As you advance, you'll discover the capabilities of the platform and extension services, including how they are packaged and priced. With the help of examples present throughout the book, you will gain a deep understanding of the platform, from its rich capabilities and technical architecture to its ecosystem and key go-to-market aspects. By the end of this IBM book, you'll be able to apply IBM Cloud Pak for Data's prescriptive practices and leverage its capabilities to build a trusted data foundation and accelerate AI adoption in your enterprise. What you will learn Understand the importance of digital transformations and the role of data and AI platforms Get to grips with data architecture and its relevance in driving AI adoption using IBM's AI Ladder Understand Cloud Pak for Data, its value proposition, capabilities, and unique differentiators Delve into the pricing, packaging, key use cases, and competitors of Cloud Pak for Data Use the Cloud Pak for Data ecosystem with premium IBM and third-party services Discover IBM's vibrant ecosystem of proprietary, open-source, and third-party offerings from over 35 ISVs Who this book is for This book is for data scientists, data stewards, developers, and data...